The effect of SBS and wax modification on stability and stiffness of stone mastic asphalt - Kök, Baha Vural; Yılmaz, Mehmet; Akpolat, Mustafa (My University, 2014)
Increasing traffic load and flow make the additive usage and new gradation quests necessary for more quality roads. In this respect using polymer additives and stone mastic asphalt are presented as a solution. However the need for using hard and polymer modified binders in stone mastic asphalt mixtures reduces workability and elevates the costs considerably. In this study the effects of using styrene-butadiene-styrene (SBS) and Sasobit both separately and together in the hot mixtures were evaluated. B 50/70 base bitumen and limestone aggregate were used for preparing the mixtures. Marshall stability and indirect tensile stiffness modulus test were applied to the mixtures prepared by base and modified binders. The Marshall test were carried out for both unconditioned and conditioned samples and hence retained Marshall stabilities was also determined. Stiffness modules were determined at three different temperatures. SBS and Sasobit together in the same mixture significantly improves stability and stiffness of the mixtures compared to containing only SBS and Sasobit. Sasobit modification increases the effectiveness of the SBS modification with respect to mechanical properties except moisture resistance.

Artan trafik yükleri ve miktarı daha sağlam yollar için katkı kullanımını ve yeni gradasyon arayışlarını gerektirmiştir. Bu bağlamda polimer katkılarının kullanımı ve taş mastik asfalt bir çözüm olarak sunulmaktadır. Fakat taş mastik asfaltlarda sert ve polimer modifiyeli bağlayıcı kullanılması gerekliliği işlenebilirliği azaltmakta ve maliyetleri artırmaktadır. Bu çalışmada sıcak karışım içinde styrene-butadiene-styrene (SBS) ve Sasobitin hem ayrı hem de birlikte kullanılmalarının etkileri incelenmiştir. Karışımların hazırlanmasında B 50/70 bitümü ve kireç taşı agrega kullanılmıştır. Katkısız ve polimer modifiyeli karışımlara Marshall stabilite ve indirek çekme rijitlik modülü deneyleri uygulanmıştır. Marshall testi hem koşullu hem de koşulsuz numunelere uygulanarak kalıcı Marshall stabiliteleri de tespit edilmiştir. Rijitlik modülü üç farklı sıcaklıkta belirlenmiştir. Aynı karışım içinde SBS ve Sasobitin birlikte kullanılması stabilite ve rijitliği ayrı kullanılmalarına göre önemli derecede iyileştirmiştir. Nem hassasiyeti dışında mekanik özellikler açısından Sasobit, SBS katkısının etkinliğini artırmıştır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot bituminous mixture; SBS; Sasobit; Stability; Stiffness; Sıcak bitümlü karışım; Stabilite; Rijitlik